Coexistence Between Chileans and Peruvians in the International Terminal (Arica) (Revista LIDER, 2018)
This study discusses the relationship between Chileans and Peruvians around the International Terminal. The study contextualized the migratory process in the current era of globalization, it also develops a characterization on the causes of the population movement from Peru to Chile, and it establishes a profile of the person of Peruvian nationality that can be foundsin the International Terminal. We outline the construction of the cultural landscape by Peruvians in Arica and the consolidation of this circuit between the northern border of Chile and the southern region of Peru. Finally, wee address a series of proposals that could generate and consolidate the instances of dialogue between the two societies.